Modality in Donald Trump’s Speech on Iran’s Nuclear Deal - Raden Rosyda Rosyda; Heriyanto; Elvi Citraresmana (Jurnal Bahasa Inggris Terapan, 2020)
This paper reports the study of Donald Trump’s Speech on Iran’s Nuclear Deal which focuses on the types of modality. In analyzing, the data are taken from Donald Trump’s Speech on Iran’s Nuclear Deal. This study employed the framework of modality proposed by Halliday and Matthiessen (2004). The results showed 30 clauses containing modality which may be classified into modalization and modulation. Modalization consists of probability and usuality, while modulation has obligation and inclination. The findings give an insight how a politician, such as Donald Trump applies modality in his speech.